Aerosolized niosome formulation containing gemcitabine and cisplatin for lung cancer treatment: optimization, characterization and in vitro evaluation - Mohamad Saimi, Norfatin Izzatie; Salim, Norazlinaliza; Ahmad, Noraini; Abdulmalek, Emilia; Abdul Rahman, Mohd Basyaruddin (Multidisciplinary Digital Publishing Institute, 2021)
Gemcitabine (Gem) and cisplatin (Cis) are currently being used for lung cancer treatment, but they are highly toxic in high dosages. This research aimed to develop a niosome formulation containing a low-dosage Gem and Cis (NGC), as an alternative formulation for lung cancer treatment. NGC was prepared using a very simple heating method and was further optimized by D-optimal mixture design. The optimum NGC formulation with particle size, polydispersity index (PDI), and zeta potential of 166.45 nm, 0.16, and -15.28 mV, respectively, was obtained and remained stable at 27 °C with no phase separation for up to 90 days. The aerosol output was 96.22%, which indicates its suitability as aerosolized formulation. An in vitro drug release study using the dialysis bag diffusion technique showed controlled release for both drugs up to 24 h penetration. A cytotoxicity study against normal lung (MRC5) and lung cancer (A549) cell lines was investigated. The results showed that the optimized NGC had reduced cytotoxicity effects against both MRC5 and A549 when compared with the control (Gem + Cis alone) from very toxic (IC50 < 1.56 µg/mL) to weakly toxic (IC50 280.00 µg/mL) and moderately toxic (IC50 = 46.00 µg/mL), respectively, after 72 h of treatment. These findings revealed that the optimized NGC has excellent potential and is a promising prospect in aerosolized delivery systems to treat lung cancer that warrants further investigation.